2005
DOI: 10.1523/jneurosci.1115-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PrPCby Adenovirus-Mediated Gene Targeting Reduces Ischemic Injury in a Stroke Rat Model

Abstract: Prion diseases are induced by pathologically misfolded prion protein (PrPSc ), which recruit normal sialoglycoprotein PrP C by a templatedirected process. In this study, we investigated the expression of PrP C in a rat model of cerebral ischemia to more fully understand its physiological role. Immunohistochemical analysis demonstrated that PrP C -immunoreactive cells increased significantly in the penumbra of ischemic rat brain compared with the untreated brain. Western blot analysis showed that PrP C protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
92
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 54 publications
2
92
0
3
Order By: Relevance
“…15 In contrast, adenovirus-mediated PrP C overexpression reduced CNS damage in a rat model of cerebral ischemia. 16 While the mechanism(s) underlying these phenomena remain unclear, such in vivo findings have lent strong support to the idea that PrP C may have a neuroprotective function.…”
mentioning
confidence: 89%
“…15 In contrast, adenovirus-mediated PrP C overexpression reduced CNS damage in a rat model of cerebral ischemia. 16 While the mechanism(s) underlying these phenomena remain unclear, such in vivo findings have lent strong support to the idea that PrP C may have a neuroprotective function.…”
mentioning
confidence: 89%
“…In the last decade a diverse range of functions has been attributed to the native PrP C protein, such as neuroprotection against cellular and systemic insults, neuritogenesis, neuronal plasticity and excitability, and memory formation and consolidation (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Noteworthy, PrP C mutations associated to CJD, fatal familial insomnia, and Gerstmann-Straussler-Scheinker disease decrease or abolish the anti-bax function in primary human neurons and breast cancer cell lines promoting programmed cell death (34).…”
mentioning
confidence: 99%
“…Recent work has shown that PrP c induces polarization in synapse development as well as in neuritogenesis in embryonic hippocampal neuron cultures (5,6). PrP c is also up-regulated after focal cerebral ischemia (7), and PrP c overexpression reduces the extent of neuronal loss after ischemic insult, suggesting that PrP c might confer a neuroprotective effect in certain contexts (8). Recent studies have also shown that PrP c is expressed on the surface of long-term repopulating hematopoietic stem cells and that PrP c -null mice have limited hematopoietic stem cell self-renewal (9).…”
mentioning
confidence: 99%